Space-time continuum in A. Blok’s cycle «Poems about the Beautiful Lady» - Temirgazina, Z.K.; Nikolayenko, S.V.; Zhakupova, G.K. (KSU publ., 2020)
The article deals with a problem about the space-time continuum on the material of the cycle of poems by A. Blok «Poems about the Beautiful Lady». The analysis of poems is presented, semiotic dominants in the space-time category are revealed. The novelty of the article lies in the fact that the space-time continuum of this cycle of poems has not been studied from the point of view of semiotics. As a result of the work it was revealed that space and time form an indissoluble unity in the cycle. The lyrical hero of Blok in most poems about a Beautiful lady occupies a position between two worlds, on the edge, on the border between this world and the other world. At the same time, in a cycle it is possible to trace finding of the Beautiful Lady in «horizontal » and «vertical» spaces. The next direction in the analysis of space-time relations was the differentiation of linear and cyclic time. All locations and stay of a Beautiful Lady are endowed with respectively positive and negative characteristics. The lyrical hero is as it were between the visible and the invisible, the revealed and the hidden, the manifest and the secret, the real and the unreal. Thus, as a result of the study, we came to the conclusion that the cycle of poems is characterized by the awareness of space and time through the prism of the experience accumulated by the lyrical hero, the expectation of a Beautiful Lady.
Keywords: space; time; chronotope; continuum; semiotics; dominants; lyrical hero; Beautiful Lady